Statistical data and metadata exchange at The Ministry of Labour and Social Affairs of Czech Republic - Abdhillah, Dwi Laksono (2023)
The SDMX standard was launched in 2001 by seven international organizations to harmonize and facilitate the exchange of inter-agency statistics and data. This paper focuses on the progress made in implementing SDMX at the Ministry of Labour and Social Affairs of the Czech Republic (MoLSA). The study highlights the importance of the SDMX web service in facilitating the exchange of statistical information between organizations and the significance of continued collaboration and cooperation between NSIs and international organizations in establishing shared standards for efficient and effective data exchange. Practical research using ESSPROS data from MoLSA was conducted in collaboration with the Czech Statistical Office to examine the process of generating SDMX files. The study revealed that the Czech Statistical Office had successfully implemented the SDMX standards to generate XML files using a desktop converter before sending them back to Eurostat.